2016
DOI: 10.1108/ijbm-03-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of service quality on customer satisfaction in private and public sector banks

Abstract: Purpose – In today’s world, with increased competition, service quality has become one of the most popular areas of academic investigation. The purpose of this paper is to examine the impact of various service quality variables on the overall satisfaction of customers and compare the private and public sector banks using a sample from India. Design/methodology/approach – With the help of forward stepwise regression, the authors explain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 36 publications
5
111
0
5
Order By: Relevance
“…The results of several studies indicate that service quality has a positive effect on satisfaction [5], [6], [7], [8]. One of these studies found that service quality has a positive significant impact on customer satisfaction.…”
Section: Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of several studies indicate that service quality has a positive effect on satisfaction [5], [6], [7], [8]. One of these studies found that service quality has a positive significant impact on customer satisfaction.…”
Section: Service Qualitymentioning
confidence: 99%
“…One of these studies found that service quality has a positive significant impact on customer satisfaction. Knowledge of [8].…”
Section: Service Qualitymentioning
confidence: 99%
“…As such, customer satisfaction is critical in ensuring business goals are achieved. The achievement of goals the customer set out to achieve without limitations results in customer satisfaction [5], which is key to customer retention [6]. However, Rauyruen and Miller [7] identified factors that impact customer satisfaction, in addition to contextual and personal aspects, price, product quality and service quality also plays a role.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Service quality is important for the survival of any bank in an era of cut‐throat competition, as consumers value efficiency and quality in retail banking (Paul et al ., ). Commercial banks have undergone tremendous technological and managerial changes (including computerization) to catch up with the pace of globalization and new business environments across the globe.…”
mentioning
confidence: 98%